The Physical Condition Level of Futsal Extracurricular Students at Sman 2 Siak Hulu, Kampar Regency: Tingkat Kondisi Fisik Siswa Ekstrakurikuler Futsal Di Sman 2 Siak Hulu Kabupaten Kampar - Fikry Hidayat; Mimi Yulianti (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
This study aims to see and measure the level of physical condition of futsal extracurricular students at SMAN 2 Siak Hulu District Kampar. This research is a research that uses a descriptive method with a quantitative approach. The subjects in this study were futsal extracurricular students of SMAN 2 Siak Hulu District Kampar, amounting to 24 people. The research instruments used were Sprint, Leg dynamometer, Sit up test, Vertical Jump, 15 minute run (Balke test), Shuttle run. The analytical technique used was to express frequency in percentage form. The results of this study indicate that the level of physical condition of the Futsal extracurricular students at SMAN 2 Siak Hulu District Kampar is less, taking into account the frequency of the level of physical condition in the poor value category,